Tinjauan Teori Semiotika Peirce Pada “Film Senyap“ - Marcel Adi Putra (Penerbit dan Percetakan, CV. Picmotiv, 2023)
Senyap Film is a documentary film. This film received a lot of rejection from various mass organizations and officials who considered this film to have communist elements, but on the other hand, namely the National Human Rights Commission and minority communities, they saw that the silent film opened up new historical facts that had previously been closed and also attempted to build awareness of reconciliation. Film is a text that is full of meaning and has multiple interpretations which is composed of iconic signs, indices and symbols that are full of meaning. This is in accordance with Peirce's idea of ​​dividing signs into three categories, namely icons, indices and symbols in creating meaning. Therefore, the author formulates the problem, namely how the construction of meaning in silent films is related to semiotics. Based on the results of interpretation using Peirce's semantic approach. icons, indices and symbols in silent films tell about the violence carried out by the perpetrators of the murder of PKI members and the heroic attitude of the perpetrators towards the murders carried out.